The devil and the dark water ebook - Turton, Stuart (2020)
PEOPLE's Best Books of the 2020s "Compulsively readable."—New York Times Book Review From Stuart Turton, author of The 7 1/2 Deaths of Evelyn Hardcastle, comes an extraordinary new locked-room murder mystery. A murder on the high seas. A remarkable detective duo. A demon who may or may not exist. It's 1634, and Samuel Pipps, the world's greatest detective, is being transported to Amsterdam to be executed for a crime he may, or may not, have committed. Traveling with him is his loyal bodyguard, Arent Hayes, who is determined to prove his friend innocent. Among the other guests is Sara Wessel, a noblewoman with a secret. But no sooner is their ship out to sea than devilry begins to blight the voyage. A strange symbol appears on the sail. A dead leper stalks the decks. Livestock dies in the night. And then the passengers hear a terrible voice, whispering to them in the darkness, promising three unholy miracles, followed by a slaughter. First an impossible pursuit. Second an impossible theft. And third an impossible murder. Could a demon be responsible for their misfortunes? With Pipps imprisoned, only Arent and Sara can solve a mystery that stretches back into their past and now threatens to sink the ship, killing everybody on board. Shirley Jackson meets Sherlock Holmes in this chilling thriller of supernatural horror, occult suspicion, and paranormal mystery on the high seas.